2013
DOI: 10.1504/ijlic.2013.052077
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital disclosure in the context of corporate governance

Abstract: The study uses content analysis to explore the relationship between board features, audit committee and ownership structures on intellectual capital (IC) disclosure whilst controlling for firm specific characteristics such as firm-size, profitability, leverage and type of auditor. This study also attempts to provide empirical evidence on the influence of corporate governance on voluntary IC information in a developing nation drawing from both the agency and institutional theories. It was found that ownership s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 41 publications
10
36
2
10
Order By: Relevance
“…Edmans (2014) claims that blockholders, play an important role in governance, because the size of their shares in the company provides an impetus to bear the costs of monitoring managers. This finding supports the results of research by Gan,et al (2013) which states that higher blockholder ownership offers what investors want, in the form of better supervision and discipline of managers.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Edmans (2014) claims that blockholders, play an important role in governance, because the size of their shares in the company provides an impetus to bear the costs of monitoring managers. This finding supports the results of research by Gan,et al (2013) which states that higher blockholder ownership offers what investors want, in the form of better supervision and discipline of managers.…”
Section: Resultssupporting
confidence: 89%
“…The results of empirical studies on the effect of blockholder ownership on corporate governance disclosure cannot be concluded. For example, Gan,et al (2013) observed a positive relationship in companies registered in Malaysia. In contrast, Al-Bassam,et al (2015) shows that blocking has a significant negative effect on disclosure of governance in companies registered in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate governance enhances reporting quality of IC which indicated the ability of company in managing assets and firm value (Al-Sartawi, 2018). Corporate governance and voluntary disclosure of IC improve investor protection and enhance the efficiency of capital market (Gan, Saleh, Abessi, & Huang, 2013).…”
mentioning
confidence: 99%
“…Board of directors independence (BODI) was measured by a dummy variable considering the value 1 if there are independent directors on the board and 0 if not. Duality of chairman/director general (DUA) was also measured by a dummy variable considering the value 1 if there is duality and 0 if not (Cerbioni and Parbonetti, 2007;Li et al, 2008;Hidalgo et al, 2011;Taliyang and Jusop, 2011;Oba et al, 2013;Gan et al, 2013). Concerning the variables relating to the ownership structure, MO is calculated by a dummy variable that took the value of 1 if managers hold a part of the capital, and '0' otherwise.…”
Section: Governance Related Variablesmentioning
confidence: 99%